The Utilization of Augmented Reality-Based Storybooks to Improve Knowledge and Skills in Handwashing with Soap - Ricko Pratama Ridzkiyanto; Andriani Metasari Br. Limbong; Dewa Ngakan Gde Wahyu Mahatma Putra; Globila Nurika (Faculty of Public Health, University of Jember in collaboration with PERSAKMI, 2022)
The number of positive confirmed cases of Covid-19 in Indonesia until June 2021 has reached 1.35 million. This condition continues to be controlled by the government to intensify the delivery of the Covid-19 vaccine, especially for educators and education. This is intended to minimize learning loss in schooling due to online learning during the face-to-face learning pandemic in 2022. Therefore, education and training for the discipline of handwashing with soap (CTPS) in breaking the transmission of covid-19 in schools are essential to be carried out massively, especially for students. This educational and training activity with a target of 22 students was carried out at SDN 1 Panji Lor, Situbondo, using augmented reality-based CTPS storybooks. The interactive discussion method was carried out to increase student participation. Knowledge improvement was measured using pre-test and post-test. Skill improvement is calculated by using the observation of CTPS practice activities. The analysis of knowledge data before and after education with the paired-sample t-test showed an increase in students' knowledge (p-value = 0.046). In addition, all students can practice the CTPS steps correctly and adequately in training activities. The use of augmented reality-based CTPS storybooks is concluded to increase students' knowledge and skills in doing good and correct CTPS.